Algorithm of Energy-Saving Control Over Hammers of Active Excavator Buckets - Liberman Yako (EDP Sciences, 2021)
The article considers the operation of excavators designed to mine hard or frozen soils. To reduce significant energy consumption, which characterizes the process, active buckets equipped with special hammers are used. Minimizing the energy consumption of such buckets can be achieved by optimally controlling their operating modes. Expressions for the energy consumed by a hammer, characteristics of its head, operating modes, soil are derived, with the minimum of the energy estimated. On the basis of those expressions, an algorithm of energy-saving control over hammers of active excavator buckets is formed and described. It determines the corresponding speed of impact of the hammer head on the soil which can be supplied to the hammer control system in the form of a command signal. The combination of all speeds when digging a track will provide the required performance of the excavator, with each speed set to the minimum, from the viewpoint of optimizing the energy consumption, necessary for the work of the hammer.